ANALISIS KINERJA KEUANGAN PADA FINTECH PENYEDIA DANA PENDIDIKAN - Adinda Satia Putri (2022)
Financial Technology or often known as Fintech is a collaboration between technology and the financial sector with the aim of providing convenience in financial transactions, including for millennials. Millennials who grew up in the era of advanced technology, makes life inseparable from technological developments. At-present, millennials dominate fintech peer-to-peer lending financiers. On the other hand, millennials also use fintech to borrow funds, one of which is for college needs. Now, there are several peer-to-peer lending fintechs that provide credit for education funds. The financial performance analysis on the fintech peer-to-peer lending provider of education funds aims to analyze its financial statements using financial ratios. As a result, it can be said that the CICIL company is the most superior company compared to the DanaCita, DanaDidik, and DanaBagus companies. This is because of the total five ratios used to assess the company's performance, CICIL shows three ratio values with the best values. Their financial performance can increase public interest and trust in borrowing funds from Fintech Peer to Peer (P2P) Lending companies. Therefore, the main task of Fintech Peer to Peer (P2P) Lending companies is to continue to improve company performance and pay more attention to financial ratios.